Ecosystem model intercomparison of under‐ice and total primary production in the Arctic Ocean. Issue 1 (27th January 2016) - Jin, Meibing; Popova, Ekaterina E.; Zhang, Jinlun; Ji, Rubao; Pendleton, Daniel; Varpe, Øystein; Yool, Andrew; Lee, Younjoo J.
Abstract: Previous observational studies have found increasing primary production (PP) in response to declining sea ice cover in the Arctic Ocean. In this study, under‐ice PP was assessed based on three coupled ice‐ocean‐ecosystem models participating in the Forum for Arctic Modeling and Observational Synthesis (FAMOS) project. All models showed good agreement with under‐ice measurements of surface chlorophyll‐a concentration and vertically integrated PP rates during the main under‐ice production period, from mid‐May to September. Further, modeled 30‐year (1980–2009) mean values and spatial patterns of sea ice concentration compared well with remote sensing data. Under‐ice PP was higher in the Arctic shelf seas than in the Arctic Basin, but ratios of under‐ice PP over total PP were spatially correlated with annual mean sea ice concentration, with higher ratios in higher ice concentration regions. Decreases in sea ice from 1980 to 2009 were correlated significantly with increases in total PP and decreases in the under‐ice PP/total PP ratio for most of the Arctic, but nonsignificantly related to under‐ice PP, especially in marginal ice zones. Total PP within the Arctic Circle increased at an annual rate of between 3.2 and 8.0 Tg C/yr from 1980 to 2009. This increase in total PP was due mainly to a PP increase in open water, including increases in both open water area and PP rate per unit area, and therefore much stronger than the changes in under‐ice PP. All models suggested that, on a pan‐Arctic scale, the fraction of under‐ice PP declined with declining sea ice cover over the last three decades. Key Points: Total primary production within the Arctic Circle increased 3.2–8 Tg C/yr Fraction of under‐ice production declined with declining sea ice cover over in Arctic Increase in total production was due to increased open water areas and production rate